وسائل الإعلام وأساليبه في الدولة العربية الإسلامية من 41 هـ / 661 م الى 218 هـ / 833 م دراسة تاريخية - الجبوري، ممدوح سالم محمد; الجبوري، محمود عباد محمد (تكريت, 2003)
Mass media in considered one of the most important civilized aspects that characterize the Islamic State. The importance of its study is due to the fact that it is one of the important means used by the state to guard its entity and security . The above mentioned reasons represent the point of departure for this research . This study adopts a distinctive historical and informational method to bridge the gap in studying civilization related to our Islamic history . The study consists of three chapters : chapter one sheds light on the objectives of information which concentrate on two important goals . The first one is to protect the Caliphate and his institutions that represent the supreme authority of state , the second one is to preserve order and stability in the state . Chapter two deals with mass media used by the Islamic State to achieve goals mentioned above . In this regard , it demonstrates each one of these means : importance and role . Chapter three deals with mass media ,its effect ,and its use . It studies the theoretical styles which were dominant . It also studies the visual scenes of these means . The study has come up with the following results : 1-In spite of the fact that nowadays mass media has modern theories and equipments which are unknown at that time , the role played by mass media in Islamic State is active in reinforcing the pillars of state in addition to other means . 2- The mass media that is adopted by the state is a purely Islamic one stems from the Islamic thought which aims to achieve all state interests . 3- The Caliphate is ultimately responsible for mass media because he is the unique decision maker and there is no administrative institution to do that . 4-A great attention was paid to mass media that leads to hope-for results . 5- A certain method according to which the heads of the excuted rebellions and carry them from one country ( area ) to another in order to disseminate such news . 6- Many techniques used to reflect the role of mass media as that in the use of colours in the flags . 7- The continuous use of poetry , letters and books to subsequent period of time proves it validity
Keywords: العالم العربي -- التاريخ الإسلامي -- وسائل الإعلام -- الخلافة الاسلامية -- نظام الحكم